Mechanisms of sex differences in atrial fibrillation: role of hormones and differences in electrophysiology, structure, function, and remodelling. Issue 3 (22nd October 2018) - Odening, Katja E; Deiß, Sebastian; Dilling-Boer, Dagmara; Didenko, Maxim; Eriksson, Urs; Nedios, Sotirios; Ng, Fu Siong; Roca Luque, Ivo; Sanchez Borque, Pepa; Vernooy, Kevin; Wijnmaalen, Adrianus P; Yorgun, Hikmet
Abstract: Atrial fibrillation (AF) is the clinically most prevalent rhythm disorder with large impact on quality of life and increased risk for hospitalizations and mortality in both men and women. In recent years, knowledge regarding epidemiology, risk factors, and patho-physiological mechanisms of AF has greatly increased. Sex differences have been identified in the prevalence, clinical presentation, associated comorbidities, and therapy outcomes of AF. Although it is known that age-related prevalence of AF is lower in women than in men, women have worse and often atypical symptoms and worse quality of life as well as a higher risk for adverse events such as stroke and death associated with AF. In this review, we evaluate what is known about sex differences in AF mechanisms—covering structural, electrophysiological, and hormonal factors—and underscore areas of knowledge gaps for future studies. Increasing our understanding of mechanisms accounting for these sex differences in AF is important both for prognostic purposes and the optimization of (targeted, mechanism-based, and sex-specific) therapeutic approaches.